ACC/AHA/SCAI/SIR/SVM 2018 Appropriate Use Criteria for Peripheral Artery Intervention - Bailey, Steven R.; Beckman, Joshua A.; Dao, Timothy D.; Misra, Sanjay; Sobieszczyk, Piotr S.; White, Christopher J.; Wann, L. Samuel; Bailey, Steven R.; Dao, Timothy; Aronow, Herbert D.; Fazel, Reza; Gornik, Heather L.; et al. (Journal of the American College of Cardiology, 2019)
The American College of Cardiology (ACC) collaborated with the American Heart Association, Society for Cardiovascular Angiography and Interventions, Society of Interventional Radiology, and Society for Vascular Medicine, along with several ACC Councils, to establish and evaluate Appropriate Use Criteria (AUC) for peripheral artery intervention (PAI). Although PAI has been the subject of prior single-society papers, this is the first multisocietal effort on the topic. To initiate the AUC process, patient scenarios that are common in clinical practice were drafted, along with assumptions and definitions for those scenarios. The scenarios were created using published guidelines, trial data, and expert opinions from within the field of peripheral artery disease. The writing group developed 45 clinical scenarios with up to 6 intervention options per scenario and categorized them into 6 general sections. A separate, independent rating panel evaluated each indication using a scoring scale from 1 to 9, thereby designating each indication as “Appropriate” (score of 7 to 9), “May Be Appropriate” (score of 4 to 6), or “Rarely Appropriate” (score of 1 to 3). Throughout the scenarios, emphasis was placed on adhering to and exhausting medical therapy to achieve maximal benefit in those situations in which symptom management was desired or incidental disease was discovered. However, situations arise in which medical therapy is insufficient, and identifying a suitable revascularization strategy is necessary. After considering factors such as symptom burden, anatomic distribution, and ischemic burden, the rating panel determined that both endovascular and surgical approaches are Appropriate in clinical scenarios involving concomitant tissue loss or end organ compromise. There was a tendency to select endovascular approaches in these scenarios, particularly in anatomic distributions below the knee and where prior endovascular or surgical revascularization has been performed. Given the dynamic landscape of cardiovascular medicine, the writing group felt it was necessary to address situations in which adjunct arterial revascularization may be necessary to facilitate other procedures such as percutaneous valve replacement or hemodynamic support. The clinical situations where this occurs often make endovascular interventions more attractive and that was reflected in the ratings. The purpose of this particular AUC is to provide guidance to clinicians who may refer patients for revascularization treatments and to interventionalists and surgeons themselves. With the field of peripheral artery disease constantly evolving, it is imperative to offer tools and resources that physicians can utilize to provide the best care for their patients.